Análise da dinâmica de risco à erosão no município de Garanhuns - PE - Ramos, Renilson Pinto da Silva (2020)
Considered one of the biggest environmental problems that humanity faces, soil erosion annually removes tons of soils from different environments, causing areas of environmental degradation. Despite being a natural phenomenon, erosion processes are intensified through human actions when they are improperly executed in discrepancy with the local levels of risk to erosion configured by their environmental system. Therefore, the possibility of decision-making by the public administration that aims to apply measures in areas with the appearance of erosion that aim to mitigate the evolution of this phenomenon is present, however this can only happen when there is information about where this environmental problem can to occur. This work seeks to understand the dynamics of erosive processes in the municipality of Garanhuns-PE on different dates, identifying existing erosive processes and relating them to the physical-natural characteristics of the municipality, together with the forms of spatial appropriation that were given to different areas of the municipality. thus adapting the methodology chosen to the reality of Garanhuns and performing a risk classification to linear erosion, as well as analyzing soil removal through diffuse runoff using the universal soil loss equation. In order to carry out these procedures, analyzes were performed through data manipulation in a Geographic Information System (GIS) environment, applying both the readjustment of the weights of the base methodology with the technical procedure of the Analytic Hierarchy Process (AHP) and in the application of the universal soil loss equation. For the maps of risk to erosion, the choice of three main classes was established, namely low risk, medium risk and high risk, while in the results of the universal soil loss equation the standard intensity definition procedure was adopted sediment removal per ton in hectares. All other data used in the work were given the role of fostering a discussion around how the municipality's physical-environmental dynamics behaves, and how this contributes to the evolution of erosive processes, including the rainfall anomaly index that helped to demonstrate the periods of greatest and least amounts of rain in the last 30 years. In 2010, low risk has 95.09 km², average risk 309.56 km², high risk class has 56.63 km², in 2015 low risk has 96.77 km², medium risk 311.80 km² and high risk 48, 71 km² and in 2018 low risk has 92, 40 km², medium risk 321.62 km² and high risk 43, 40 km². In the universal soil loss equation, the levels of material removal reached a very severe level, in terms of average; some areas of the municipality lose approximately 129 tons of soil annually. So that it is possible to avoid this possibility and mitigate the damage from existing erosion, the public administration could apply different palliative measures in areas that have a high risk of erosion, thus contributing to a better maintenance of the space in the municipality of Garanhuns.